Acceptability of the Layer Poultry Farm Management System - Sabado, Wilber B. (International Journal of Computing Sciences Research, 2024)
Purpose   – The web-based application called the Layer Poultry Farm Management System is aimed at helping the farmers and even owners of a layer poultry farm to efficiently and effectively manage their resources and production including the inventories and finances. Method – This study used Descriptive-Developmental design which showed the processes of developing, testing, and evaluating the Farm Management System.  Descriptive research involves testing and uses logical methods to arrive at generalization. Results – The Layer Poultry Farm Management System’s functionality was rated 4.16 with the interpretation of Very Acceptable, reliability was rated 3.90 with the interpretation of Very Acceptable, system’s usability was rated 4.43 with the interpretation of Very Acceptable, system’s maintainability was rated 3.94 with the interpretation of Very Acceptable. Conclusion – The system’s finance management module has successfully tracked the sales and expenses of the layer poultry farm; the inventory management module has successfully monitored the eggs, culls, layers, brooders houses, etc; the reports management module has successfully displayed the finance and inventory data; and the settings module has successfully provided the admin the ability for system configurations. Recommendations – To add SSL for better security of the system for web hosting. Also, to integrate the Internet of Things into the system. Research Implications – This research seeks to promote innovations and the development of new features that can benefit farmers. Practical Implications – This research proves that technology integration enhances work efficiency. Social Implications – This research shows opportunities for skilled work in using technology. Also, about the potential reduction of manual labor.